Predictors of Antenatal Care, Skilled Birth Attendance, and Postnatal Care Utilization among the Remote and Poorest Rural Communities of Zambia: A Multilevel Analysis - Jacobs, Choolwe; Moshabela, Mosa; Maswenyeho, Sitali; Lambo, Nildah; Michelo, Charles (Frontiers in Public Health, 2017)
Abstract Objective: Optimal utilisation of maternal health care services is associated with reduction of mortality and morbidity for both mothers and their neonates. However, deficiencies and disparity in the use of key maternal health services within most developing countries still persist. We examined patterns and predictors associated with the utilisation of specific indicators for maternal health services among mothers living in the poorest and remote district populations of Zambia. Methods: A cross-sectional baseline household survey was conducted in May 2012. A total of 551 mothers with children between the ages 0 – 5 months were sampled from 29 catchment areas in four rural and remote districts of Zambia using the Lot Quality Assurance Sampling method. Using multilevel modelling, we accounted for individual and community level factors associated with utilisation of maternal health care services, with a focus on antenatal care (ANC), skilled birth attendance (SBA), and postnatal care (PNC). Results: Utilisation rates of focused ANC, SBA and PNC within 48 hours were 30%, 37%, and 28%, respectively. The mother’s ability to take an HIV test and receiving test results, and uptake of Intermittent Preventive Treatment for malaria were positive predictors of focused ANC. Receiving ANC at least once from skilled personnel was a significant predictor of SBA and PNC within 48 hours after delivery. Women who live in centralised rural areas were more likely to use SBA than those living in remote rural areas. Conclusion: Utilisation of maternal health services by mothers living among the remote and poor marginalized populations of Zambia is much lower than the national averages. Finding that women that receive ANC once from a skilled attendant among the remote and poorest populations are more likely to have a SBA and PNC, suggests the importance of contact with a skilled health worker even if it is just once, in influencing use of services. Therefore, it appears that in order for women in these marginalised communities to benefit from SBA and PNC, it is important for them to have at least one ANC provided by a skilled personnel, rather than non skilled health care providers.